Pertanggungjawaban Pidana Terhadap Pelaku Pemerasan Dan Atau Pengancaman Menurut Undang-Undang Nomor 19 Tahun 2016 Tentang Perubahan Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik Dan Kuh Pidana (Studi: Putusan Nomor 7/Pid.Sus/2017/Pn.Snb) - Libert Hamonangan Habeahan; Alvi Syahrin; M Hamdan; M Eka Putra (Iuris Studia: Jurnal Kajian Hukum, 2021)
The number of cases of extortion and / or threats using information technology means that the author is interested in conducting research with the title "Criminal Liability Against Extortion and Or Threats Perpetrators According to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Information. Electronic Transactions and the Criminal Code ”(Study: Decision Number 7 / Pid.Sus / 2017 / Pn.Snb) The formulation of the problem in this research is (1) How is the criminal act of extortion and / or threats according to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and the Criminal Code, (2) How is criminal responsibility for extortion and / or threats through electronic media according to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information And Electronic Transactions and the Criminal Code. (3) What are the judges' legal considerations in Decision Number 7 / Pid.Sus / 2017 / PN.Snb? This research is normative and descriptive analysis. The legal theory used in this research is the Criminal Liability Theory. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique is library research (library research). Data analysis is qualitative. The formulation of the provisions of Article 27 paragraph (4) which combines the criminal act of extortion and / or threats in one provision, whereas in the Criminal Code the criminal act of extortion is regulated in Article 368 while threatening is regulated in Article 369 of the Criminal Code. Extortion is a common crime. Extortion is how to do it by using violence or threats of violence. Threatening is an absolute complaint. Criminal responsibility for extortion and / or threats through electronic media according to the ITE Law and the Criminal Code because someone has committed a criminal act. Criminal liability is essentially a mechanism established by the Criminal Code to react to violations of certain acts. Judges' legal considerations in the Court Decision 7 / Pid.Sus / 2017 / PN.Snb, that based on the facts at the trial, and the testimony of witnesses, the defendant has been legally and convincingly proven to have committed the crime of extortion and threats of violating Article 27 paragraph 4 UU ITE UU ITE Jo Article 45 paragraph (4) In the trial, the Panel of Judges did not find anything that could eliminate criminal responsibility, either as a justification and / or excuse, so the Defendant had to be accountable for his actions. The defendant is able to be responsible, so he must be found guilty and sentenced to punishment.